Meneladani Sosok Al Ghazali Dari Indonesia Sebagai Ayah Dan Guru Terbaik (Kh. Abdullah Bin Nuh) - Novita Misika Putri; Tantan Hermansah; Novi Andayani Praptiningsih (Magister Komunikasi Universitas Sultan Ageng Tirtayasa, 2022)
AbstractFigures in the development of Islam are considered to be able to provide good examples for students and generations after. The example is obtained through direct interaction with the character as well as through the character's written work for the next generation. This study aims to describe the figure of KH. Abdullah bin Nuh who became a role model as the best father and teacher known as Al Ghazali from Indonesia. This research uses the historical method. The historical method is the process of critically examining and analyzing, recordings, and relics of the past. This study uses a library or bibliographic approach (library research) because it relies on documents, archives, and books related to the biography of KH. Abdullah bin Noah. Then the data of the findings were analyzed descriptively which was reviewed theoretically. The results of the study show that KH. Abdullah bin Nuh was an admirer of Imam Al Ghazali and admitted that he was a student of Al Ghazali even though he did not study directly. Therefore he was dubbed the figure of Al Ghazali from Indonesia. KH. Abdullah bin Nuh is a good role model for students and their families as well as generations after. His personality is polite but full of humor and simple even though he has position and power.Keywords: KH. Abdullah bin Nuh, Al Ghazali from Indonesia, Best Father and Teacher